2011
DOI: 10.1016/j.bpj.2011.03.065
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Functionally Significant Conformational Equilibria in Adenylate Kinase by High Concentrations of Trimethylamine Oxide Attributed to Volume Exclusion

Abstract: The effect of an inert small molecule osmolyte, trimethyl amine N-oxide (TMAO), upon the conformational equilibria of Escherichia coli adenylate kinase was studied using time-resolved FRET. The relative populations of open and closed clefts between the LID and the CORE domains were measured as functions of the concentrations of the substrate ATP over the concentration range 0-18 mM and TMAO over the concentration range 0-4 M. A model was constructed according to which the enzyme exists in equilibrium among fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 54 publications
(62 reference statements)
2
39
0
Order By: Relevance
“…For the opening−closing event, it has been shown with time-resolved FRET experiments that TMAO addition reduces the distance between the side chains of residue 142 in the ATPlid and residue 203 in the CORE subdomain. 51 This nicely illustrates that closed conformations are favored in presence of TMAO. A 1 H− 15 N HSQC spectrum of AK eco in presence 0.35 M TMAO is of high quality (Supporting Information Figure 1C) and the overall chemical perturbations referenced to AK eco under regular buffer conditions are relatively small (Supporting Information Figure 1D).…”
Section: ■ Results and Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…For the opening−closing event, it has been shown with time-resolved FRET experiments that TMAO addition reduces the distance between the side chains of residue 142 in the ATPlid and residue 203 in the CORE subdomain. 51 This nicely illustrates that closed conformations are favored in presence of TMAO. A 1 H− 15 N HSQC spectrum of AK eco in presence 0.35 M TMAO is of high quality (Supporting Information Figure 1C) and the overall chemical perturbations referenced to AK eco under regular buffer conditions are relatively small (Supporting Information Figure 1D).…”
Section: ■ Results and Discussionmentioning
confidence: 83%
“…12,29 . 52 Since FRET experiments have shown that TMAO affects the open/closed equilibrium by stabilizing closed conformations, 51 we conclude that both the hydrogen bond and TMAO perturbations affect the open/closed equilibrium. In all cases, the chemical shifts of apo AK eco appear in-between those of the two perturbed states.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is possible for proteins where a significant difference in SAS area exists between the structural states involved. Urea has opposite effects on these dynamics to those of osmolytes like TMAO, which favor the closed and more compact state of Adk at the expense of the open, more expanded state (10,38). Previous studies involving the FIGURE 13 (A) Illustrative projection amplitudes (X) for three amino acid residues (57, red; 124, blue; and 176, green).…”
Section: Discussionmentioning
confidence: 99%
“…Adk undergoes a large conformational change in response to ligand binding that shuttles the protein into a closed and active conformation where phosphoryl transfer occurs (Rhoads & Lowenstein, 1968). Because of its favorable properties -specifically, its tendency to yield excellent NMR spectra (Ådén & Wolf-Watz, 2007;Schrank et al 2009), catalysis of a reversible reaction, and large conformational changes (Müller et al 1996;Müller & Schulz, 1992) -Adk has emerged as one of the principal model systems for analyzing the linkage between dynamics and enzymatic turnover (Arora & Brooks, 2007;Hanson et al 2007;Nagarajan et al 2011;Schrank et al 2009;Shapiro et al 2009Shapiro et al , 2000Shapiro & Meirovitch, 2006). In an extensive multi-approach effort, the Kern laboratory has shown that substrate-free Adk from the hyperthermophilic bacterium Aquifex aeolicus samples 'closed like' structures (Henzler-Wildman et al 2007).…”
Section: Adkmentioning
confidence: 99%